The Effectiveness of the Discovery Learning Method as a Solution to Improve Elementary School Students’ Learning Outcomes - Agusalim (Jurnal Wawasan Sarjana, 2024)
This study was motivated by the low learning outcomes of Grade V students at SD Negeri 1 Nganganaumala in the subject of Natural and Social Sciences (IPAS), which were caused by unvaried and predominantly passive teaching methods. The aim of this research was to examine the effectiveness of the discovery learning method in improving student learning outcomes. This study employed a Classroom Action Research (CAR) approach involving 21 students as subjects. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data collection techniques included observation of learning activities, student achievement tests, and documentation. Data were analyzed both qualitatively and quantitatively by examining improvements in student engagement and test scores from the pre-cycle to the second cycle. The results showed a significant improvement in student learning outcomes, with the class mastery increasing from less than half of the students achieving passing scores in the pre-cycle to nearly all students achieving mastery by the second cycle. Furthermore, students’ motivation and participation in the learning process also showed positive growth. In conclusion, the discovery learning method is effective in improving student learning outcomes and fostering a more active, creative, and enjoyable learning process. Therefore, this method is recommended for continuous implementation in elementary schools to enhance learning quality.